Stress test precision and bank competition - Diego Moreno; Tuomas Takalo (Bank of Finland, 2024)
We study a competitive banking sector in which banks choose the level of risk of their asset portfolios and, upon the public disclosure of stress test results, raise funding by promising investors a repayment. We show that competition forces banks to choose risky assets so as to promise investors high repayments, and to gamble on favorable stress test results. Increasing stress test precision increases banks' asset riskiness but also improves allocative efficiency. When risk taking is not too sensitive to the precision of information, maximal transparency maximizes both stability and surplus. In contrast, when banks exercise market power assets are less risky, while opacity maximizes banks' stability and, when the social cost of bank failure is sufficiently large, the surplus as well. Our results in overall highlight the need to take into account the structure of banking industry when designing stress tests.
urn:nbn:fi-fe202402025459
Keywords: G21; G28; D83; 330; financial stability; stress tests; bank transparency; banking regulation; bank competition